2006
DOI: 10.1007/s00259-005-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of brain astrocytoma with 1-11C-acetate

Abstract: ACE appears to be a promising tracer for use in the detection of primary astrocytomas, but is of limited value in the differentiation of high- and low-grade astrocytomas. ACE is complementary to FDG for the diagnosis and characterisation of astrocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Studies are underway to develop 18 F-fluoro tracers, as 18 F has a half life of 110 min compared to 20 min for 11 C, thus allowing the capture of higher resolution images. While AA and DHA-based radiotracers have not yet been used to image brain tumors, PET imaging using 1-11 C-acetate and 2-18 F-fluoro-2-deoxy-D-glucose tracers have shown promise for the detection of primary astrocytomas in humans [123]. Furthermore, standardized uptake values that correlated with astrocytoma histological grade were observed with 2-18 F-fluoro-2-deoxy-D-glucose [123].…”
Section: Neuroimaging Of Aa and Dha: Potential For Astrocytoma Detectmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are underway to develop 18 F-fluoro tracers, as 18 F has a half life of 110 min compared to 20 min for 11 C, thus allowing the capture of higher resolution images. While AA and DHA-based radiotracers have not yet been used to image brain tumors, PET imaging using 1-11 C-acetate and 2-18 F-fluoro-2-deoxy-D-glucose tracers have shown promise for the detection of primary astrocytomas in humans [123]. Furthermore, standardized uptake values that correlated with astrocytoma histological grade were observed with 2-18 F-fluoro-2-deoxy-D-glucose [123].…”
Section: Neuroimaging Of Aa and Dha: Potential For Astrocytoma Detectmentioning
confidence: 99%
“…While AA and DHA-based radiotracers have not yet been used to image brain tumors, PET imaging using 1-11 C-acetate and 2-18 F-fluoro-2-deoxy-D-glucose tracers have shown promise for the detection of primary astrocytomas in humans [123]. Furthermore, standardized uptake values that correlated with astrocytoma histological grade were observed with 2-18 F-fluoro-2-deoxy-D-glucose [123]. We propose that the altered uptake/ turnover of AA and DHA in malignant glioma compared to normal brain tissue could be exploited for the imaging and grading of astrocytomas.…”
Section: Neuroimaging Of Aa and Dha: Potential For Astrocytoma Detectmentioning
confidence: 99%
“…[ 11 C]Acetate has recently been used to detect increased glial tumor metabolism (Liu et al, 2006;Tsuchida et al, 2008). 2-18 F-fluoroacetate has been successful in detecting glioblastoma in a mouse model system (Marik et al, 2009).…”
Section: In Vivo Imaging Probesmentioning
confidence: 99%
“…Dienel et al reported that 2-14 C-acetate preferentially labeled glial tumors grown in rat brain and human glioma and meningioma explants (23). Our previous study showed that 1-11 C-acetate detected astrocytomas better than did 18 F-FDG (22). No clinical studies have so far compared 1-11 C-acetate and 18 F-FDG PET in the diagnosis of meningioma.…”
mentioning
confidence: 99%
“…1-11 C-acetate has been used for the detection of renal carcinoma (18), nasopharyngeal carcinoma (19), prostate cancer (20), hepatoma (21), and astrocytoma (22). The possible mechanisms of tumor uptake of 1-11 C-acetate include impaired tricarboxylic acid cycle activity or the distribution of tracer among the various intermediate metabolites (19) or incorporation of tracer in the tumor through the anabolic pathways in fatty acid and sterol synthesis (20).…”
mentioning
confidence: 99%